2019
DOI: 10.3233/jad-181089
|View full text |Cite
|
Sign up to set email alerts
|

Putative Survival Advantages in Young Apolipoprotein ɛ4 Carriers are Associated with Increased Neural Stress

Abstract: Inheritance of a single copy of the apolipoprotein E (APOE) 4 allele increases risk of Alzheimer's disease (AD) by 3-4-fold, with homozygosity associated with a 12-16-fold increase in risk, relative to 3 allele homozygosity. There is a decreased risk associated with the APOE 2 allele. The pathological consequence of APOE genotype has led to intense efforts to understand the mechanistic basis of the interplay between APOE status and loss of synapses. Numerous 4 allele-related associations have been reported wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 166 publications
1
39
0
Order By: Relevance
“…21 With respect to plasticity, in particular, it has been suggested that possession of the ε4 allele is associated with higher levels of synaptic macromolecular turnover, which may facilitate early development but also may stress basic cellular neuroplasticity mechanisms. 8 This would explain the improved early performance at the expense of a decreased performance during aging. 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 With respect to plasticity, in particular, it has been suggested that possession of the ε4 allele is associated with higher levels of synaptic macromolecular turnover, which may facilitate early development but also may stress basic cellular neuroplasticity mechanisms. 8 This would explain the improved early performance at the expense of a decreased performance during aging. 22…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, it is unclear what role APOE plays across the life span of an individual with DS, given that DS is associated with both intellectual disability in early life and an ultra-high risk for AD in later life. 1 The APOE gene plays a central role in the metabolism of lipids, 8 the principal components of myelin, and myelination is a crucial process in white matter development. 5,9 The early development of white matter pathways has been associated with faster reaction times in an attentional eye-tracking task, the gap-overlap task.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are reports showing that APOE4 genotype may improve neuronal performance and survival during fetal development, infancy, and youth at the expense of decreased capacity in old age. 9 Dementia has not been described as a symptom of D2HGA1, perhaps because the patients described so far have not lived long enough, no formal natural history studies have been carried out for D2HGA1 or because the diagnosis of dementia is difficult in patients with ID. This report serves to shed light on the importance of a multidisciplinary approach to patients with unclear diagnosis, the importance of updated family histories, genetic investigations, and expanding the differential diagnosis to include inborn errors of metabolism in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is because it has been identified as a genetic risk factor for AD in the general population ( Kim et al, 2009 ; Ritchie et al, 2019 ). The ε4 allele is an AD risk factor, the ε3 allele neutral, and the ε2 allele is protective; one copy of the ε4 allele increases risk of AD by 3-4-fold, two copies of ε4 by 12-16-fold, relative to possessing two copies of the ε3 allele, while there is a decreased risk associated with the ε2 allele ( Smith et al, 2019 ). The risk factor potentially operates via the effect of APOE on amyloid-β metabolism.…”
Section: Linking Variability In Early Cognitive Development and Adultmentioning
confidence: 99%
“… Dean et al (2014) compared magnetic resonance imaging measurements of white matter myelin water fraction and grey matter volume in healthy infant carriers and non-carriers of the ε4 allele between 2 and 25 months, and found decreased rate of growth in myelin in mid and posterior brain regions, in areas preferentially affected by AD in adulthood. Smith, Ashford and Perfetti (2019) suggest that possession of the ε4 allele is associated with higher levels of synaptic macromolecular turnover, which may produce greater early plasticity but also stress basic cellular neuroplasticity mechanisms. For both APP and APOE , then, there are links between development and pathological ageing.…”
Section: Linking Variability In Early Cognitive Development and Adultmentioning
confidence: 99%